Teachers’ judgment accuracy concerning consistent and inconsistent student profiles - Südkamp, Anna; Praetorius, Anna-Katharina; Spinath, Birgit (Teaching and teacher education, 2018)
Research on teachers' judgment accuracy has focused on teacher judgments of single student characteristics. We analyzed differences in teachers' judgment accuracy concerning students with consistent and inconsistent cognitive and socio-emotional profiles (i.e., profiles of cognitive abilities, self-concept, motivation, and anxiety). Based on test scores and self-reports of N = 743 students, we identified one inconsistent and two consistent profiles. Judgments of N = 43 teachers yielded only three consistent student profiles, indicating that teachers perceived student profiles to be more consistent than they really were. Contrary to our expectations, teachers' judgments were not more accurate for consistent student profiles.
Online 10 October 2017
Gesehen am 24.04.2019